Prediksi Penjualan Produk Menggunakan Data Mining Dengan Metode K-Nearest Neighbor Pada PT. Terang Abadi Raya - Endang Supandi; putu sugiartawan (INFOTEKS (Information Technology, Computer and Sciences), 2022)
Terang Abadi Raya is a lighting and cable distributor company that has various types of goods, with the many types of products to be sold the company has difficulty in determining which products are the most sold in the market. This makes it difficult for the marketing department to offer products to be sold. PT. Terang Abadi Raya has various types of products based on sales data for the last 5 years, using the K-Nearest Neighbor prediction can make it easier for companies to plan sales. To find out the best-selling sales using the maining data classification and the K-Nearest Neighbor method. The results of this study are predictions of sales of the best-selling electric tools as many as 5 items. Based on the accuracy value of the best selling product sales classification of 99,50074%.